An Examination of the Central Life Interest Scale - Maurer, John G.; Vredenburgh, Donald J.; Smith, Richard L. (Academy of Management Journal, 1981)
This paper investigates the Central Life Interest (CLI) scale using four distinct respondent groups. Attention is focused on ability of the items to discriminate respondents across groups as well as internal consistency and dimensionality of the scale. The results raise questions about the psychometric properties of this scale.